Radiopharmacy education in Brazil - Ralph Santos-Oliveira; Marta De Souza Albernaz (Archives of Global Professionals, 2014)
The number of schools of pharmacy has been increasing each year in Brazil. From 2002 to 2013 over 300 new schools were opened in Brazil with a final number of 415 schools of pharmacy in operation around the country. Of these schools, only 28 schools offer a course in radiopharmacy (7.77%). However, the demand for such trained professionals has grown exponentially in Brazil, especially following amendment 49 (February 2006) that broke the monopoly on the production, distribution, and marketing of short half-life radiopharmaceuticals, and the recent constitutional amendment project 517/2010, which was approved in the last instance and is waiting for final approval by the President. Thus, in this scenario, there are a total of 417 radiopharmacy services across the country waiting for qualified professionals to fill posts. However, while there are insufficient trained professionals, radiopharmacy services under the aegis of Agencia Nacional de Vigilancia Sanitaria - Brazilian Health Surveillance Agency allow biomedical scientists and biologists to perform specialized functions as developed in radiopharmacy services without the presence of radiopharmacists.